Risk factors that influenced Diabetic Kidney Disease (DKD) among patients with Chronic Kidney Disease (CKD) In Hospital Universiti Sains Malaysia (HUSM) Kubang Kerian, Kelantan / Mahiran Muhammad - Muhammad, Mahiran (2012)
Diabetic nephropathy has become a highly prevalent health problem in patients. A case study has been carried out to modeling the risk factors between diabetic and non diabetic in Chronic Kidney Disease among HUSM Kubang Kerian patients, Kelantan. The study was conducted in three month (12 weeks), which was on 5th March 2012 to 5th June 2012. The objectives of this study were to determine the prevalence of Diabetic Kidney Disease among Chronic Kidney Disease in HUSM in 2011, to describe the socio-demographic and clinical characteristics of diabetic kidney disease patients and to develop multiple logistic model for diabetic kidney disease that associated with the most influencing among independent variables. Data collection was done at the Unit rekod in HUSM to obtain details on socio-demographic and clinical variables which includes systolic blood pressure, diastolic blood pressure, urea level, haemoglobin level and uric acid level. The prevalence of diabetic nephropathy in 2011 at HUSM was found to be 57.02%. The frequency table for gender showed 55.9% of female patients with diabetic kidney disease. The study also found that uric acid was the most influenced factor to DKD. Overall, in HUSM Kubang Kerian, females have higher percentage of Diabetic nephropathy compared to males although males were reported having the higher risk of diabetic kidney disease